2022
DOI: 10.3389/fphar.2022.1016981
|View full text |Cite
|
Sign up to set email alerts
|

The protective activity of genistein against bone and cartilage diseases

Abstract: Genistein, a natural isoflavone rich in soybean and leguminous plants, has been shown various biological effects, such as anti-inflammation, anti-oxidation, anti-cancer, and bone/cartilage protection. Due to the structural similarity to estrogen, genistein exhibits estrogen-like activity in protecting against osteoporosis and osteoarthritis. Furthermore, genistein has been considered as an inhibitor of tyrosine kinase, which has been found to be dysregulated in the pathological development of osteoporosis, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…Clinically, symptom relief becomes the effective strategy to treat OA. TNFα and IL-1βplay a central role in the pathological development of OA [127]. The inhibition of inflammatory responses is an effective therapeutic strategy for managing OA.…”
Section: The Protective Activities Of Naringin Against Osteoarthritis...mentioning
confidence: 99%
“…Clinically, symptom relief becomes the effective strategy to treat OA. TNFα and IL-1βplay a central role in the pathological development of OA [127]. The inhibition of inflammatory responses is an effective therapeutic strategy for managing OA.…”
Section: The Protective Activities Of Naringin Against Osteoarthritis...mentioning
confidence: 99%
“… Fang et al (2018) reported the inhibitory effect of wogonin on IL-1β-induced inflammatory factors and enzymes that promote ECM degradation; in addition, these authors also observed that wogonin upregulated the expression of type II collagen. Genistein, a flavonoid extracted from soybean, has been shown to be effective in preventing osteoarthritis and osteoporosis ( Wu and Liu, 2022 ). In IDD, genistein was shown to increase the secretion of type II collagen and aggrecan and reduce the expression of inflammatory factors by inhibiting the P38 MAPK pathway ( Ge et al, 2020 ) ( Figure 4 ).…”
Section: The Application Of Natural Products To Control Inflammationmentioning
confidence: 99%
“…The study involving ultrasonication resulted in a high encapsulation efficiency of over 95%, but in vivo assays have not been performed. The second study involved a formulation containing medium chain triglycerides (MCT) oil as a medium and a combination of cholecalciferol and genistein (a polyphenolic isoflavone, that along with its many other effects, , also stimulates bone formation and inhibits resorption, thus positively affecting osteoporosis and osteoarthritis). As in the studies discussed above, in vivo investigations have not been performed.…”
Section: Noninvasive and Microinvasive Delivery Routesmentioning
confidence: 99%